2018
DOI: 10.5935/abc.20180199
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value and Clinical Use of Myocardial Perfusion Scintigraphy in Asymptomatic Patients after Percutaneous Coronary Intervention

Abstract: BackgroundThe role of myocardial perfusion scintigraphy (MPS) in the follow-up of asymptomatic patients after percutaneous coronary intervention (PCI) is not established.ObjectivesTo evaluate the prognostic value and clinical use of MPS in asymptomatic patients after PCI.MethodsPatients who underwent MPS consecutively between 2008 and 2012 after PCI were selected. The MPS were classified as normal and abnormal, the perfusion scores, summed stress score (SSS), and summed difference score (SDS) were calculated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
0
1
2
Order By: Relevance
“…In a study conducted with non-ST-segment elevation myocardial infarction patients, it was reported that there was a low correlation between CAD severity and CRI-I, but CRI-II did not show a significant relationship [19]. On the other hand, previous studies have reported a positive correlation between the myocardial damage and extent of CAD [20][21][22]. In the current study, CRI levels were higher in patients with ischemia.…”
Section: Discussioncontrasting
confidence: 56%
“…In a study conducted with non-ST-segment elevation myocardial infarction patients, it was reported that there was a low correlation between CAD severity and CRI-I, but CRI-II did not show a significant relationship [19]. On the other hand, previous studies have reported a positive correlation between the myocardial damage and extent of CAD [20][21][22]. In the current study, CRI levels were higher in patients with ischemia.…”
Section: Discussioncontrasting
confidence: 56%
“…Em resumo, a medicina nuclear é fundamental para o manejo de doenças cardiovasculares. [7][8][9][10][11] na cardiologia clínica de rotina, mas não é a primeira linha de abordagem para pacientes com COVID-19. Apesar disso, seus procedimentos podem eventualmente ajudar no manejo desses pacientes.…”
Section: Referênciasunclassified
“…Um outro estudo brasileiro 43 Considerando-se os AUC publicados em 2009, que contam com um critério especifico para suspeita de revascularização incompleta além dos critérios relacionados ao tempo para realização do exame após ICP, consideramos que pacientes com suspeita de revascularização incompleta não deveriam ser avaliados conjuntamente com os demais pacientes assintomáticos no cenário pós ICP, pois é bem estabelecido o papel da CPM no cenário de suspeita de revascularização incompleta. Em nosso estudo tivemos vários pacientes em que após a revascularização de um vaso com obstrução importante havia dúvida quanto à necessidade ou não de revascularização de obstruções duvidosas, e tais pacientes foram classificados segundo o critério 56, referente a suspeita de revascularização incompleta e não segundo os critérios 59 e 60, referentes ao tempo desde a ICP.…”
Section: Or = 1 Multivariadaunclassified